Alkene Vicinal Difluorination: From Fluorine Gas to More Favoured Conditions - Doobary, Sayad; Lennox, Alastair J. J. (Synlett, 2020)
Vicinal difluorinated alkanes are entities relevant to medicinal chemistry that are accessed through the difluorination of alkenes. This reaction has advanced from the use of highly reactive and unsafe reagents, which provide poor functional-group tolerance and selectivity, to the use of safer and more selective reagents that facilitate access to a broader scope of substrates. In this review article, we describe the details of these developments.1 Introduction2 Strategy 1: Ambiphilic Fluorine Sources3 Strategy 2: Oxidant and Fluoride4 Conclusions and Outlook
Keywords: fluorination; alkenes; oxidation; hypervalent iodine; electrochemistry; difluorination